The Influence of Emotional Intelligence on Job Burnout and Job Performance: Mediating Effect of Psychological Capital - Gong, Zhun; Chen, Yuqi; Wang, Yayu (Frontiers in Psychology, 2019)
How does emotional intelligence (EI) affect job performance and job burnout? Direct or indirect? What role does psychological capital play? This study surveyed 450 employees of various enterprises through questionnaires. Results are as follows: (1) Employees’ EI has a positive predictive effect on psychological capital and job performance, and it is negatively correlated with job burnout; (2) psychological capital has a negative predictive effect on job burnout and a positive predictive effect on job performance; and (3) psychological capital plays a mediating role in the relationship between EI and job burnout/performance. Results of this study may contribute to develop EI theories in organizational behavior field. As for enterprises, improving the EI of employees will help to improve their psychological capital, and high psychological capital will lead to positive job performance and less job burnout.